Pengaruh Current Ratio, Debt To Equity Ratio, Earning Per Share, terhadap Kinerja Keuangan - Alan Wijaya Sitohang; Bayu Wulandari (Mahesa Research Center, 2020)
This journal aims to test whether, Current Ratio (CR), Debt To Equity Ratio (DER), Earning Per Share (EPS) have an influence on financial performance in manufacturing companies listed on the Indonesia Stock Exchange (BEI). This journal is a type of quantitative descriptive research, which uses data from 144 manufacturing companies listed on the Indonesia Stock Exchange multiplied by 3 consecutive years of financial statements 2016-2018. The data used are the financial statements of each sample company published on the website www.idx.co.id. The results showed that partially CR is significant and influences financial performance (ROA), the results of statistical tests show that DER is not significant to ROA, from the test results that partially EPS is significant to ROA.